IMPLEMENTASI NILAI VASUDHAIVA KUTUMBAKAM UNTUK MEMPERKUAT TOLERANSI DALAM BUDAYA ORGANISASI DI INDIKA FOUNDATION - Ditya Agustia; Kurniasari, Ni Gusti Ayu Ketut; Putra, I Made Jaya Negara Suarsa (UHN IGB Sugriwa Denpasar, 2026)
Indika Foundation is an institution that develops an organizational culture based on tolerance and brotherhood. This study aims to examine how Indika Foundation builds and implements the Vasudhaiva Kutumbakam values in its organizational culture. The study used a qualitative approach with descriptive methods through semi-structured interviews with the Indika Foundation team. The results show that the Vasudhiva Kutumbakam values are built through open communication, exemplary leadership, behavioral guidelines (Rainbow Behavior), and collaborative habits. Its implementation is seen in inclusive work practices, respect for diversity, regular reflection, and equal cooperation with partners. These values have been internalized as basic assumptions of the organization and form a work culture that is tolerant, inclusive, and based on universal brotherhood.